Distress tolerance in social versus solitary college student drinkers. (November 2015) - Williams, Catherine L.; Vik, Peter W.; Wong, Maria M.
Abstract: Low distress tolerance has been an inconsistent predictor of alcohol-related consequences in college students, but its relationships to depression and coping motives for alcohol have received stronger support. Research on college students who drink heavily in isolation suggests that this population is more likely to have a greater number and severity of alcohol-related problems, depression, and coping motives. Solitary heavy drinkers were therefore hypothesized to have lower distress tolerance than other drinkers. This study examined differences in self-reported and behavioral distress tolerance across two groups of university students: those who endorsed heavy solitary drinking (20.1%) versus those who endorsed other types of drinking. Students completed a self-report measure (Distress Intolerance Self-Report, or DISR) and behavioral measure of distress tolerance (Paced Auditory Serial Addition Test, or PASAT). Students who reported drinking heavily in isolation differed from other students on the DISR, F (1, 132) = 4.645, p  = .033, η 2  = .034, but not on the PASAT, F (1, 132) = 0.056, p  = .813. These students also endorsed more coping motives for alcohol. Distress tolerance did not predict drinking consequences directly, yet a mediation model linking distress tolerance to consequences through coping motives supports previous findings of distress tolerance as a distal, indirect predictor of drinking problems. The unique characteristics of solitary binge drinkers and the significance of distress tolerance as an indirect predictor of alcohol-related consequences are discussed. Highlights: Reported differences in distress tolerance across types of college student drinkers Students varied by self-report but not behavioral distress tolerance measures. Solitary binge drinkers had more coping motives than other drinkers. Coping mediated the relationship between distress tolerance and alcohol problems.